Has COVID-19 Affected Cancer Screening Programs? A Systematic Review - Alkatout, Ibrahim; Biebl, Matthias; Momenimovahed, Zohre; Giovannucci, Edward; Hadavandsiri, Fatemeh; Salehiniya, Hamid; Allahqoli, Leila (Frontiers in Oncology, 2021)
Background: Health care services across the world have been enormously affected by the onset of the coronavirus disease 2019 (COVID-19). Services in oncology have been curtailed because medical services have been focused on preventing the spread of the virus and maximizing the number of available hospital beds. The present study was designed to investigate the impact of COVID-19 on cancer screening. Methods: Databases such as Medline, Web of Science Core Collection (Indexes = SCI-EXPANDED, SSCI, A & HCI Timespan) and Scopus were searched comprehensively for articles published until January 2021. The keywords used were COVID-19 and cancer screening, Articles dealing with cancer screening in the COVID-19 pandemic were included in the review. Results: The review comprised 18 publications. The impact of COVID-19 was categorized into four dimensions: a significant decline in cancer screening and pathology samples, the cancer diagnosis rate, an increase in advanced cancers, mortality rate and years of life lost (YLLs). Conclusion: Cancer screening programs have been clearly interrupted since the onset of the COVID-19 disease. The anticipated outcomes include delayed diagnosis and marked increases in the numbers of avoidable cancer deaths. Urgent policy interventions are needed to handle the backlog of routine diagnostic services and minimize the harmful effects of the COVID-19 pandemic on cancer patients.